Probability, queueing theory and reliability engineering - Haribaskaran, G (Laxmi Pub, 2006)
Probability, queueing theory and reliability engineering / Haribaskaran, G. -- Kolkata: Laxmi Pub., 2006 519.2 H281e2 2nd ed. No. of Copies : 1